Australian Transnational Union Solidarity through Union-Building in Timor-Leste. (May 2019) - Hannington-Pinto, Daniel
Abstract : Australian union support for the development of an organised labour movement in independent Timor-Leste has received scant attention. Looking to address this gap in the literature, this article focuses on the contributions of two individual activists between 2002 and 2003: Didge McDonald, from the Liquor, Hospitality and Miscellaneous Union; and the Maritime Union of Australia's Michael Killick. Their role in the development of Timorese unions was a crucial counterweight to the exploitation of domestic workers by foreign businesses – a phenomenon expedited by the macroeconomic implications of the broader United Nations state-building mission. Considered through the prism of nation-building at the civil society level, Australian union assistance to Timor-Leste is presented as a valuable example of how cross-border partnerships following the model of New Labour Internationalism can help workers challenge the growing reach of transnational capital.